China and India: learning from history, building the present and avoiding narratives on their "unescapable clash" - Cioculescu, Șerban Filip; Petre, Silviu (2013)
Abstract: This paper examines the difficult relations between the biggest Asian states and the most populous countries in the world: China and India. Starting from the historical experiences of crisis and war, the study is focusing on the strategic culture and on the decision-makers' visions on their own state and the other one. In spite of the fact that both countries have peaceful official doctrines and try to normalize their relations, People Republic of China’s spectacular rise in power, its assertiveness concerning the borders, the support for Pakistan and some more or less accidental events like border violations, could precipitate an armed clash between the two Asian neighbors. The balance of power at the world level, with the USA and China oscilating between rivalry and cooperation, balance of power versus engagement, could determine India and China to reshape their strategies and policies on the long term